John and Elaine at Wells Cathedral - Unknown:::Creator::::::::::::
John and Elaine Steinbeck sit by a pond at Wells Cathedral, Also know as the Cathedral Church of Saint Andrew, an Anglican cathedral in Wells, Somerset, England. A carnival is going on behind them. They hired a girl named Juliette, who could walk so John could write; 'You should see her in her zucchini.' See also 3-005 Original in safe. B&W